Analisis Pengaruh Produk Domestik Bruto dan nilai ekspor terhadap Inflasi di 5 Negara ASEAN (Indonesia, Filipina, Singapura, Malaysia, dan Thailand) - Hidayanto, Taufik Nur; Riyardi, Agung (JURNAL ILMIAH EDUNOMIKA, 2024)
Purpose: to understand and analyze the influence of gross domestic product (GDP) and export value on inflation in five countries in ASEAN. Methodology: The analysis method in this study is econometric analysis of panel data regression from 2018 to 2022 in 5 ASEAN countries (Indonesia, Philippines, Singapore, Malaysia, and Thailand) using e-Views software. Results: The results of the research partially show that the variables gross domestic product (GDP) (X1) and export value (X2) have a significant and positive influence on inflation in the five main ASEAN countries. The test results together also show that there is a significant positive influence of the variables gross domestic product (GDP) (X1) and export value (X2) on inflation. Applications/Originality/Value: This research uses five ASEAN countries, namely Indonesia, Malaysia, Singapore, Thailand, and the Philippines, as research objects, where the use of these countries has never been carried out in previous research. Then the added value of this research can be seen in the choice of GDP as one of the variables, where GDP is one of the main variables in determining the inflation rate